High Adsorption Performance of Graphene Oxide Doped Double Network Hydrogels for Removal of Azo Dyes from Water and Their Kinetics - Tamer, Yasemin; Ozeren, Mehmet Derya; Berber, Hale (SPRINGER, 2021)
The removal of azo dyes, which release dangerous aromatic amines by reductive cleavage, are a crucial environmental issue in the field of wastewater treatment. To achieve an effective disposal, nanocomposite hydrogels owing enhanced adsorption capacity and mechanical strength can be designed as polymeric adsorbents. In this study, novel poly(acrylamide-co-itaconic acid)/GO-polyethyleneimine (P(AAm-IA)/GO-PEI) double network nanocomposite hydrogel adsorbents were synthesized in the presence of as-prepared graphene oxide (GO) nanosheets to be used in the effective adsorption of azo dyes; cationic crystal violet (CV) and anionic direct red 23 (DR23). To determine the effect of GO amount in removing azo dyes from aqueous medium, two-dimensional graphene oxide (GO) having high amount of oxygen-containing functional groups with 1.16 nm thickness and 0.88 nm interlayer distance, was successfully prepared via the modified Hummers method. When 0.2 wt% GO was added to the polymeric network structure, the adsorption capacity increased from 390.6 to 774.46 mg g(-1) for CV. As well as, it was determined that the presence of PEI made the nanocomposite hydrogel sensitive for the adsorption of anionic DR 23, with an adsorption capacity of 349.29 mg g(-1). The adsorption capacity was found to increase with increasing GO amount, initial dye concentration, and contact time but decreased with the adsorbent amount. The adsorption is well-described by pseudo-second-order kinetics and the equilibrium data fitted well with the Langmuir isotherm model for CV and Freundlich isotherm model for DR 23 adsorption. The reausability performance of the nanocomposite hydrogels was carried out by adsorption-desorption studies and a removal efficiency of 99-84% and 75-61% for CV and DR23 was obtained after five cycles.
Keywords: Graphene oxide; Double network hydrogel; Water purification; Adsorption; Azo dyes; DIRECT RED 23; CRYSTAL VIOLET; AQUEOUS-SOLUTION; IONS ADSORPTION; ANIONIC DYES; CATIONIC DYE; ADSORBENTS; EQUILIBRIUM; ISOTHERMS; COMPOSITE; Engineering; Polymer Science